Análise dos componentes do ciclo de vida dos dados na matriz curricular dos cursos de biblioteconomia : um estudo comparado - Anjos, Renata Lemos dos (2019)
Since the first scientific journals were published, scientific communication was limited to the publishing and disclosure of the results, product of the scientific investigations in the form of scientific journals articles. With the significant advancement of the Digital Technologies of Information and Communication, increasingly data is being generated upon the completion of the academic-scientific activities causing the scientific communication to be inserted in the scope of the phenomenon known as e-Science. This new scenario demands able professionals to act in the curation process of the researched data during all the steps in the cycle of life, bringing observations about the empowerment of the librarians in dealing with the treatment of data arising from these investigations. On this perspective, the present research proposes to analyze in what ways the information professionals, with an emphasis in librarians, are being capacitated to this reality, at the undergraduate level. Given the aforementioned, it was asked: how the inherent components to each step of the Data Life Cycle for Information Science are being contemplated in the subjects taught in the Brazilian undergraduate course of Library Science? It is configured as a research exploratory and bibliographic of qualitative and quantitative nature, through the comparative method through the inference of content analysis. It was observed that none of the Librarianship courses analyzed possess mandatory curricular components that approach the fourth scientific paradigm. Although they have skills that can be used - applied and/or appropriate throughout the Information Science Data Life cycle, with greater adherence to the Cycle Recovery Phase. Thus, it is suggested the reformulation of the curricular matrices of the Brazilian Librarianship courses, in order to add curricular components that approach e-Science and present it as a field of action for data librarians.